CFD simulation of empty fuel tanks separation from a trainer jet. Issue 10 (6th August 2020) - Olejnik, Aleksander; Dziubiński, Adam; Kiszkowiak, Łukasz
Abstract : Purpose: This study aims to create 6-degree of freedom (SDOF) for computational fluid dynamics (CFD) simulations of body movement, and to validate using the experimental data for empty tank separation from I-22 Iryda jet trainer. The procedure has an ability to be modified or extended, to simulate, for example, a sequential release from the joints. Design/methodology/approach: A set of CFD simulations are calculated. Both the SDOF procedure and the CFD simulation settings are validated using the wind tunnel data available for the aircraft. Findings: The simulation using designed procedure gives predictable results, but offers availability to be modified to represent external forces, i.e. from body interaction or control system without necessity to model the control surfaces. Practical implications: The procedure could be used to model the separation of external stores and design the deployment of anti-radar chaff, flares or ejection seats. Originality/value: The work presents original work, caused by insufficient abilities of original SDOF procedure in ANSYS code. Additional value is the ability of the procedure to be easily modified.